Adynamic Bone Decreases Bone Toughness During Aging by Affecting Mineral and Matrix. (6th October 2015) - Ng, Adeline H; Omelon, Sidney; Variola, Fabio; Allo, Bedilu; Willett, Thomas L; Alman, Benjamin A; Grynpas, Marc D
ABSTRACT: Adynamic bone is the most frequent type of bone lesion in patients with chronic kidney disease; long‐term use of antiresorptive therapy may also lead to the adynamic bone condition. The hallmark of adynamic bone is a loss of bone turnover, and a major clinical concern of adynamic bone is diminished bone quality and an increase in fracture risk. Our current study aims to investigate how bone quality changes with age in our previously established mouse model of adynamic bone. Young and old mice (4 months old and 16 months old, respectively) were used in this study. Col2.3Δtk (DTK) mice were treated with ganciclovir and pamidronate to create the adynamic bone condition. Bone quality was evaluated using established techniques including bone histomorphometry, microcomputed tomography, quantitative backscattered electron imaging, and biomechanical testing. Changes in mineral and matrix properties were examined by powder X‐ray diffraction and Raman spectroscopy. Aging controls had a natural decline in bone formation and resorption with a corresponding deterioration in trabecular bone structure. Bone turnover was severely blunted at all ages in adynamic animals, which preserved trabecular bone loss normally associated with aging. However, the preservation of trabecular bone mass and structure in old adynamic mice did not rescue deterioration of bone mechanical properties. There was also a decrease in cortical bone toughness in old adynamic mice that was accompanied by a more mature collagen matrix and longer bone crystals. Little is known about the effects of metabolic bone disease on bone fracture resistance. We observed an age‐related decrease in bone toughness that was worsened by the adynamic condition, and this decrease may be due to material level changes at the tissue level. Our mouse model may be useful in the investigation of the mechanisms involved in fractures occurring in elderly patients on antiresorptive therapy who have very low bone turnover. © 2015 American Society for Bone and Mineral Research.